PENERAPAN AKAD IJARAH PADA BISNIS JASA PENYEWAAN ALAT PESTA DALAM PRESPEKTIF EKONOMI ISLAM KECAMATAN TEGALSARI, KABUPATEN BANYUWANGI - Rufi’ah (Jurnal Ekonomi Syariah Darussalam, 2025)
The purpose of this study is to determine the application of the ijarah contract in the party equipment rental service business in Tegalsari Village, Tegalsari District, Banyuwangi Regency. And to find out how the Islamic Economic perspective on the party equipment rental service business. This type of research is a qualitative case study with a single case design. The results of this study indicate that the application of this ijarah is ijarah 'amal, namely the provision of compensation for a job or expertise carried out by someone. The application of the ijarah contract in this business is not in accordance with the ijarah contract in terms of ujrah or costs because it still uses a down payment system at the beginning of the rental period and pays off the costs at the end of the rental period, if the rental of the party equipment is canceled then the down payment will be forfeited. Based on the research conducted, this study concludes that the implementation of the ijarah contract in the party equipment rental business, from an Islamic economic perspective, is appropriate. The ijarah contract, as practiced in the party equipment rental business, complies with Islamic law, with clear terms of work, form, timeframe, and price (ujrah), and the services being rented are considered permissible.